Analysis Of The Implementation Of Tax Amnesty In Indonesia - Wartoyo, Wartoyo; Usman, Usman (AL-QARDH, 2024)
The purpose of this study is to analyze the implementation of the tax amnesty policy in Indonesia by describing the indicators of its success on macroeconomic variables. This study uses a descriptive qualitative approach with the type of case study research method and data analysis technique using literature study. The results of the study show that the tax amnesty program based on Law Number 11 of 2016 has not succeeded in significantly increasing taxpayer compliance, and the realization of revenue from this program is still below the set target. However, the implementation of this program has a positive impact on Indonesia's economy, including increasing liquidity, improving the rupiah exchange rate, lowering interest rates, and stimulating increased investment. Thus, while tax amnesty has not been optimal in improving overall tax compliance, the program has made a significant positive contribution to several aspects of the national economy.